The knowledge of skin care rules in patients with acne vulgaris (Journal of Face Aesthetics, 2019)
Acne vulgaris is one of the most common dermatological disease which may present with disturbed epidermal barrier function, exacerbated by drugs used to treat acne, both general and local. The instructing patients with acne in the selection of appropriate cosmetic products, significantly improves their quality of life. The aim of the study was to gain the knowledge of acne patients about the skin care principles. The study involved 80 patients suffering from acne vulgaris and showed the need to conduct education in the field of proper care of the acne skin.
Keywords: acne vulgaris; amolients; skin care